Development of summary indices of antenatal care service quality in Haiti, Malawi and Tanzania - Ashley Sheffel; Scott Zeger; Rebecca Heidkamp; Melinda Kay Munos (BMJ Open)
Introduction Measuring quality of care in low-income and middle-income countries is complicated by the lack of a standard, universally accepted definition for ‘quality’ for any particular service, as well as limited guidance on which indicators to include in measures of quality of care, and how to incorporate those indicators into summary indices. The aim of this paper is to develop, characterise and compare a set of antenatal care (ANC) indices for facility readiness and provision of care.Methods We created nine indices for facility readiness using three methods for selecting items and three methods for combining items. In addition, we created three indices for provision of care using one method for selecting items and three methods for combining items. For each index, we calculated descriptive statistics, categorised the continuous index scores using tercile cut points to assess comparability of facility classification, and examined the variability and distribution of scores.Results Our results showed that, within a country, the indices were quite similar in terms of mean index score, facility classification, coefficient of variation, floor and ceiling effects, and the inclusion of items in an index with a range of variability. Notably, the indices created using principal components analysis to combine the items were the most different from the other indices. In addition, the index created by taking a weighted average of a core set of items had lower agreement with the other indices when looking at facility classification.Conclusions As improving quality of care becomes integral to global efforts to produce better health outcomes, demand for guidance on creating standardised measures of service quality will grow. This study provides health systems researchers with a comparison of methodologies commonly used to create summary indices of ANC service quality and it highlights the similarities and differences between methods.